Rekonstruksi Makna Ummah dalam Perspektif Tafsir Tematik Al-Qur’an - Nudia Amburika; Novi Fitriani (SENTRI: Jurnal Riset Ilmiah, 2025)
The term ummah is one of the key concepts in the Qur’an, encompassing a wide range of meanings and a broad semantic scope that shapes the identity, social structure, and religious orientation of the Muslim community. This study aims to analyze the meaning of ummah through semantic and thematic approaches by examining all Qur’anic verses containing this term and its derivatives. The research employs a qualitative method based on library research, with the Qur’an as the primary source and Arabic lexicons alongside other supporting literature as secondary sources. The findings reveal that the Qur’anic concept of ummah can be classified into four main semantic categories: community, leadership, religion, and time. Additionally, seven lexemes derived from the same root as ummah were identified umam (communities), imām (leader), aimmah (leaders), umm (mother), ummahāt (mothers), ummī (unlettered), and amāma (in front of) with a total frequency of 116 occurrences throughout the Qur’an. Furthermore, the study highlights six ideal characteristics of the ummah according to the Qur’an: muslimah (submissive), wasata (moderate), wahidah (united), qāimah (upright), muqtaṣidah (balanced), and qānitah (devout). This research contributes to the development of Qur’anic semantic studies and expands contemporary Islamic scholarship’s understanding of the dynamic conceptualization of ummah within the Qur’anic worldview.